A preliminary study on the lead uptake capacity of Gracilariopsis bailinae (Zhang et Xia). - Primavera, Karlo H
The lead uptake of Gracilariopsis bailinae (gulaman) was measured and compared to the lead uptake capacity of its agar extract. the amount of lead remaining in water was measured as well. Lead treatments were at 300 breveg/l, 400 breveg/l, and 500 breveg/l lead concentration in seawater with daily sampling for four days., Gracilariopsis bailinae bound all the available lead in water except in the 500 breveg/l lead treatment, which could be near the maximum contamination level where it can bind all available lead. However, total amount of lead in agar was very low (1) compared to that of the same weight (breveg Pb/g) of Gracilariopsis bailinae. This is due to the low sulfate content of agar, which is the means of taking up lead. Gracilariopsis bailinae and its agar extract's uptake of lead were active and did not release the lead back to the water. Maximum lead uptake was achieved within the first day of exposure of Gracilariopsis bailinae and its agar extract. Although a significant amount of lead (0-52 of total lead introduced) was lost to precipitation, complexes, and adherence to surfaces, under the given conditions, Gracilariopsis bailinae was effective in taking up dissolved lead because it takes up lead quickly and does not release it back to the water. This implies that human consumption of fresh Gracilariopsis bailinae harvested near areas of high lead contamination is not safe.